The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/nau.24422
|View full text |Cite
|
Sign up to set email alerts
|

Voiding conditions, renal and bowel function in a cohort of adults with spina bifida

Abstract: Aim To map voiding patterns, degree of continence, use of drugs for voiding disorders, kidney function and surgical interventions but also the bowel function in a near‐total regional cohort of adults with spina bifida aged more than or equal to 18 years. Methods All individuals more than or equal to 18 years of age with spina bifida registered at a regional outpatient clinic (n = 219) were invited to participate, of which 196 persons were included. Bladder and bowel function were assessed according to question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Bladder and bowel regimes were assessed with NSCIR (Levi & Ertzgaard, 1998), and part of the results are presented in Table 3. More in‐depth results will be presented in a separate article (Ehrén, Lindbo, Gabrielsson, Bendt, & Seiger, 2020 accepted for publication).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bladder and bowel regimes were assessed with NSCIR (Levi & Ertzgaard, 1998), and part of the results are presented in Table 3. More in‐depth results will be presented in a separate article (Ehrén, Lindbo, Gabrielsson, Bendt, & Seiger, 2020 accepted for publication).…”
Section: Methodsmentioning
confidence: 99%
“…More in-depth results will be presented in a separate article (Ehrén, Lindbo, Gabrielsson, Bendt, & Seiger, 2020 accepted for publication).…”
Section: Structural and Medical Characteristicsmentioning
confidence: 99%
“…One hundred forty‐one persons had a myelomeningocele and 13 persons had a non‐myelomeningocele lesion of whom 10 persons were diagnosed with a lipomeningocele and 3 persons with SB occulta. As we in our recently published study 7 found persons in the group with non‐myelomeningocele lesions with urologic/bowel problems, we included all persons in the study group in this survey. Neuropsychological tests from Wechsler Adult Intelligence Scale®—Fourth Edition (WAIS‐IV), known to be sensitive for common cognitive problems in the population with SB 3 were used in the examination of a relationship to urological problems 8 .…”
Section: Methodsmentioning
confidence: 99%
“…6 A more detailed study of the function of the urinary tract and the bowel function in the cohort has also been performed, describing voiding conditions, complications, renal function, urological interventions and bowel function/dysfunction. 7 When analyzing the urological complications, it became apparent that some patients had difficulties to maintain necessary routines for managing voiding and bowel function, which may be related to their cognitive challenges.…”
Section: Introductionmentioning
confidence: 99%